Implementasi Pembelajaran Musik Dan Gerak Pada Guru PAUD Di Kecamatan Parongpong, Kabupaten Bandung Barat - Kurniawati, Leli; Putri, Riva Ananda; Afifah, Anindya Alya; Kamil, Siti Wardah Khofifah (Institut Agama Islam Negeri Ponorogo, 2023)
This study aims to find out how teachers implement music and movement learning in early childhood education in Parongpong District, West Bandung Regency, West Java. With a case study methodology, a qualitative research design was applied. Then observation and literature research are utilized as data collection methods. Descriptive qualitative analysis is the method of data analysis that is employed. The study's findings demonstrate that teachers have effectively incorporated music and movement into early childhood learning through appropriate stimulus, variety, expression, tempo, and enthusiasm in line with their pedagogical, personal, social, and professional competence as teachers of early childhood education.